Effects of calcium and magnesium silicate on the absorption of silicon and nutrients in wheat - Sarto, Marcos Vinicius Mansano; Lana, Maria do Carmo; Rampim, Leandro; Rosset, Jean Sérgio; Sarto, Jaqueline Rocha Wobeto; Bassegio, Doglas (Semina: Ciências Agrárias, 2019)
Wheat is a plant that accumulates silicon (Si). The application of silicon to the soil may influence the absorption of nutrients by the plant and, therefore, its nutritional balance. In this study, we aimed to evaluate the effects of calcium and magnesium silicate (CaSiO3/MgSiO3) on the ability of wheat (Triticum aestivum L.) to utilize silicon and absorb nutrients from soils collected in the state of Paraná, Brazil. The experiment was carried out in a greenhouse using 8-L plastic pots and three types of soil. Treatments were arranged in randomized blocks (3 Ã— 5 factorial design): three soils [Rhodic Acrudox (Ox1), Rhodic Hapludox (Ox2), and Arenic Hapludult (Ult)], five silicate rates (0, 1, 2, 4, and 6 t ha-1 of calcium/magnesium silicate), and four replications were performed. The effects of calcium and magnesium silicate on the concentrations of Si, N, P, K+, Ca2+, Mg2+, S, Cu2+, Zn2+, Fe2+, and Mn2+ within leaves were evaluated. Silicon concentrations in wheat leaves and stems increased with increasing rates of calcium and magnesium silicate applied to the soil. Wheat shoots accumulated averages of 28.2% (Ox1), 60.61% (Ult), and 74.14% (Ox2) of the Si from the silicate applied to the soil. Silicate fertilization increased the amount of Ca+2 and Mg+2 within leaves and reduced the amount of Zn2+ and Mn2+ within leaves. Calcium and magnesium silicate prevented excessive amounts of Mn2+ from being absorbed by wheat, improving the balance in the absorption of this nutrient.